PENGARUH PENYEBAB KEGAGALAN BERWIRAUSAHA TERHADAP PEMBELAJARAN DARI KEGAGALAN BERWIRAUSAHA DAN DAMPAKNYA TERHADAP KINERJA UMKM - Majdina, Nur; Jalaludin, Engga; Waliamin, Janusi; Latifah, Firda Zahro; Hayati, Husnul (Universitas Prof. Dr. Hazairin SH, 2024)
The main objective of this research is to examine the influence of the causes of entrepreneurial failure by using two types of causes of entrepreneurial failure (internal causes and external causes) on learning from entrepreneurial failure and its impact on the performance of SMEs in DKI Jakarta. The research method used in this research is a quantitative research method using a survey with the analytical tool used, namely Smart PLS version 3.0. which aims to examine the variables that cause internal failure, the causes of external failure, learning from entrepreneurial failure and its impact on business performance variables. The research results show that the variable learning from failure has a significant positive effect on business performance. Likewise, the variables that cause entrepreneurial failure from internal factors have a positive and significant effect on learning from entrepreneurial failure. However, in contrast to the results of testing variables that cause failure from external factors on learning from entrepreneurial failure, it shows that there is no influence on the causes of entrepreneurial failure from external factors on learning from entrepreneurial failure. It is hoped that this research can provide suggestions and input, especially for SMEs, so that they can turn entrepreneurial failures into lessons to improve business performance. This research also has several limitations, including that the SME business sector in this research is still too general, and this research only uses subjective performance measures.